Symmetric single-input eccentric tube robot (ETR) for manual use - Mayer Juliane; Dumancic Marcel; Pott Peter P. (Current Directions in Biomedical Engineering)
Concentric tube robots (CTR) have gained popularity in robotic research due to their potential for smaller instrument sizes, enhanced dexterity and reduced trauma. However, CTR control can be complex, with tip direction and curvature being kinematically coupled. To address this, a symmetric eccentric tube robot (ETR) is presented, where three identical pre-curved wires are arranged in parallel and constrained by an outer sheath. Instrument curvature is controlled by a single input angle. This study aims to demonstrate the suitability as manually actuated instrument. A model for curvature as a function of input angle is presented, and a prototype ETR with an outer diameter of 1 mm is assembled and evaluated. The results show that the ETR follows the expected shape, the curvature decreasing with the separation angle in an almost linear way that may be perceived as intuitive and predictable by the human user. However, some unsteady behavior (snapping) is observed, which may be addressed by preventing torsion of the wires through mechanical means. The simplified model neglecting the sheath stiffness provides precise enough predictions for the working space of a manual ETR. The findings suggest that manual ETRs have potential applications in superficial interventions, such as injections, arthroscopy, or ophthalmic surgery, where their curved section can be beneficial in comparison to current straight needles. Further research could explore interlocking mechanical designs to prevent torsion or modular setups for enhanced functionality.